Forgiveness of Judges: Local Wisdom in the Concept of National Criminal Law - Zuhri, Muhammad Fakhruddin (Walisongo Law Review (Walrev), 2019)
Criminal law, as an instrument of guarding public order, has two functions. The first one is as general function to regulate life and to organize procedures in society. The second one is as particular function to protect legal interests from crime by giving criminal punishment as sanctions for the perpetrators. Conceptually, forgiveness of the judge emerges to modify rigid legal certainty towards flexible legal certainty. This departs from several cases that have actually fulfilled the formulation of criminal offenses, but their actions are not feasible to be sentenced. Therefore, in the concept of the National criminal law, the Draft of Criminal Code (RKUHP) makes a new formula containing local wisdoms that regulate the possibility of forgiveness of the judge to several cases that are improperly being convicted. This paper focuses on the concept of forgiveness of the judge that cannot be separated from the local wisdom values, including religious values and legal wisdoms living in society.